2012
DOI: 10.7763/ijmlc.2012.v2.165
|View full text |Cite
|
Sign up to set email alerts
|

Offline Character Recognition System Using Artificial Neural Network

Abstract: Advancement in Artificial Intelligence has lead to the developments of various "smart" devices. The biggest challenge in the field of image processing is to recognize documents both in printed and handwritten format. Character recognition is one of the most widely used biometric traits for authentication of person as well as document. Optical Character Recognition (OCR) is a type of document image analysis where scanned digital image that contains either machine printed or handwritten script input into an OCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…N Vasudeva et al suggested a method with more appropriate results in comparision of matching with normalized wordimage [40]. Preprocessing focuses on deduction of the noise resulting due to the scanner quality used for capturing the image.…”
Section: Basic Stages In Character Recognitionmentioning
confidence: 99%
“…N Vasudeva et al suggested a method with more appropriate results in comparision of matching with normalized wordimage [40]. Preprocessing focuses on deduction of the noise resulting due to the scanner quality used for capturing the image.…”
Section: Basic Stages In Character Recognitionmentioning
confidence: 99%
“…Nisha Vasudeva et al [7] briefly discuss the back propagation with feature extraction for character recognition. Authors compare different font's accuracy for different hidden nodes with a single hidden layer.…”
Section: Fazlul Kader and Kaushik Debmentioning
confidence: 99%
“…The number of iterations in back propagation is called epochs used in Back Propagation to solve the weight matrix feasible for all input matrix. The comparison of epochs and accuracy is given in below figure (from [7]):…”
Section: No Of Epochs Used To Calculate the Weight Matrixmentioning
confidence: 99%
“…They have used the Back propagation Neural Network for efficient recognition where the errors were corrected through back propagation and rectified neuron values were transmitted by feed-forward method in the neural network of multiple layers. [4] Kauleshwar Prasad, et.al, focused on recognition of English alphabet in a given scanned text document with the help of Neural Networks. Using Matlab Neural Network toolbox, also they have attempted to recognize handwritten characters by projecting them on different sized grids.…”
Section: Related Workmentioning
confidence: 99%